2021
DOI: 10.1177/17407745211015924
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials site recruitment optimisation: Guidance from Clinical Trials: Impact and Quality

Abstract: Background/Aims: Participants are integral to the success of any clinical research study, yet participant recruitment into clinical trials poses ongoing and complex challenges. It is widely accepted and recognised that clinical trial sites often find it difficult to meet recruitment goals, both in terms of accrual targets and timelines. This can impact the validity of trials or cause major delays for research. There are very few frameworks available to clinical trial sites to improve recruitment. The GREET pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Our findings echo those reported by Levett et al [ 20 ] who found that sites that had a supportive and defined research trial structure for recruitment in place consistently had better recruitment rates than those that did not. Having a clear recruitment strategy right at the start and assigned responsibilities is an important enabler to recruitment success [ 21 ]. We observe that sites that were more efficient in recruitment dedicated more staff hours to recruitment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings echo those reported by Levett et al [ 20 ] who found that sites that had a supportive and defined research trial structure for recruitment in place consistently had better recruitment rates than those that did not. Having a clear recruitment strategy right at the start and assigned responsibilities is an important enabler to recruitment success [ 21 ]. We observe that sites that were more efficient in recruitment dedicated more staff hours to recruitment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al [ 11 ] reported that GPs located in a high SES area recruited at a lower rate than those in lower SES which contrasts with that reported in ASPREE. Gaining access to research participants in rural or remote areas has been identified as one of the top ten barriers to recruitment [ 21 ], and this is being addressed in Australia through the development of tele-trials and rural practice-based research networks such as the PARTNER network [ 23 ]. It was observed that the study coordinator made more visits to rural sites (7.5 compared to 4.6 for non-rural sites), and this was likely to have contributed to the recruitment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Time taken for funding and ethics approval would need to be considered and proactively buffered for in the planning stages as the start of recruitment could be delayed and even impact the sample size, especially when the inclusion criteria are time-sensitive ( 80 82 ). Although ample preparations have been made, the study was delayed by a few months as the sudden introduction of government-mandated restricted movements in Brunei had halted most research operations when the second wave of the COVID-19 pandemic hit Brunei in August 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular and Thoracic Surgery Wards at the University Clinical Center Maribor treat over 4000 individuals annually and it is estimated that roughly 1400 individuals meet the inclusion criteria. However, based on the fact that, in general, at most 30% of participants (or less) consent to the clinical study, 39 we assume that the final number of subjects willing to participate will be much lower. Regarding sample size requirements for the present study, public registries of clinical trials were reviewed.…”
Section: Methodsmentioning
confidence: 99%